RESISTING THROUGH CITIZEN JOURNALISM: A CRITICAL DISCOURSE ANALYSIS ON THE BLACK LIVES MATTER MOVEMENT ON TWITTER - Khansa Salsabila; Ida Rochani Adi (Rubikon : Journal of Transnational American Studies, 2022)
The Black Lives Matter movement in 2020 has emerged through the help of social media and citizen journalism in spreading the news, responding to the incident, and mobilizing the protest against police brutality and racial discrimination against African Americans. Citizen journalism has become an alternative for Twitter users who distrust American journalism from mainstream news media. This study examined tweets of citizen journalism to see the discourse of American journalism on Twitter. Using Van Dijk’s Critical Discourse Analysis (CDA), this study finds positive and negative aspects of citizen journalism. The first is that citizen journalism is an online resistance tool of protesters against news institutions where they can voice their opinions and deny news institutions’ negative portrayal. The second, citizen journalism, is a tool for news institutions in responding to the protesters’ resistance. It is because protesters lack a solid and consistent perception of the issue. The rejection of news institutions and journalists is no longer immediate attention for them as soon as police officers attack news crews.The Black Lives Matter movement in 2020 has emerged through the help of social media and citizen journalism in spreading the news, responding to the incident, and mobilizing the protest against police brutality and racial discrimination against African Americans. Citizen journalism has become an alternative for Twitter users who distrust American journalism from mainstream news media. This study examined tweets of citizen journalism to see the discourse of American journalism on Twitter. Using Van Dijk’s Critical Discourse Analysis (CDA), this study finds positive and negative aspectse of citizen journalism. The first is that citizen journalism is an online resistance tool of protesters against news institutions where they can voice their opinions and deny news institutions' negative portrayal. The second, citizen journalism, is a tool for news institutions in responding to the protesters' resistance. This is because protesters lack a solid and consistent perception of the issue, and the rejection of news institutions and journalists is no longer primary attention for them as soon as police officers attack news crews.The Black Lives Matter movement in 2020 has emerged through the help of social media and citizen journalism in spreading the news, responding to the incident, and mobilizing the protest against police brutality and racial discrimination against African Americans. Citizen journalism has become an alternative for Twitter users who distrust American journalism from mainstream news media. This study examined tweets of citizen journalism to see the discourse of American journalism on Twitter. Using Van Dijk’s Critical Discourse Analysis (CDA), this study finds positive and negative aspectse of citizen journalism. The first is that citizen journalism is an online resistance tool of protesters against news institutions where they can voice their opinions and deny news institutions' negative portrayal. The second, citizen journalism, is a tool for news institutions in responding to the protesters' resistance. This is because protesters lack a solid and consistent perception of the issue, and the rejection of news institutions and journalists is no longer primary attention for them as soon as police officers attack news crews.The Black Lives Matter movement in 2020 has emerged through the help of social media and citizen journalism in spreading the news, responding to the incident, and mobilizing the protest against police brutality and racial discrimination against African Americans. Citizen journalism has become an alternative for Twitter users who distrust American journalism from mainstream news media. This study examined tweets of citizen journalism to see the discourse of American journalism on Twitter. Using Van Dijk’s Critical Discourse Analysis (CDA), this study finds positive and negative aspectse of citizen journalism. The first is that citizen journalism is an online resistance tool of protesters against news institutions where they can voice their opinions and deny news institutions' negative portrayal. The second, citizen journalism, is a tool for news institutions in responding to the protesters' resistance. This is because protesters lack a solid and consistent perception of the issue, and the rejection of news institutions and journalists is no longer primary attention for them as soon as police officers attack news crews.The Black Lives Matter movement in 2020 has emerged through the help of social media and citizen journalism in spreading the news, responding to the incident, and mobilizing the protest against police brutality and racial discrimination against African Americans. Citizen journalism has become an alternative for Twitter users who distrust American journalism from mainstream news media. This study examined tweets of citizen journalism to see the discourse of American journalism on Twitter. Using Van Dijk’s Critical Discourse Analysis (CDA), this study finds positive and negative aspectse of citizen journalism. The first is that citizen journalism is an online resistance tool of protesters against news institutions where they can voice their opinions and deny news institutions' negative portrayal. The second, citizen journalism, is a tool for news institutions in responding to the protesters' resistance. This is because protesters lack a solid and consistent perception of the issue, and the rejection of news institutions and journalists is no longer primary attention for them as soon as police officers attack news crews.The Black Lives Matter movement in 2020 has emerged through the help of social media and citizen journalism in spreading the news, responding to the incident, and mobilizing the protest against police brutality and racial discrimination against African Americans. Citizen journalism has become an alternative for Twitter users who distrust American journalism from mainstream news media. This study examined tweets of citizen journalism to see the discourse of American journalism on Twitter. Using Van Dijk’s Critical Discourse Analysis (CDA), this study finds positive and negative aspectse of citizen journalism. The first is that citizen journalism is an online resistance tool of protesters against news institutions where they can voice their opinions and deny news institutions' negative portrayal. The second, citizen journalism, is a tool for news institutions in responding to the protesters' resistance. This is because protesters lack a solid and consistent perception of the issue, and the rejection of news institutions and journalists is no longer primary attention for them as soon as police officers attack news crews.The Black Lives Matter movement in 2020 has emerged through the help of social media and citizen journalism in spreading the news, responding to the incident, and mobilizing the protest against police brutality and racial discrimination against African Americans. Citizen journalism has become an alternative for Twitter users who distrust American journalism from mainstream news media. This study examined tweets of citizen journalism to see the discourse of American journalism on Twitter. Using Van Dijk’s Critical Discourse Analysis (CDA), this study finds positive and negative aspectse of citizen journalism. The first is that citizen journalism is an online resistance tool of protesters against news institutions where they can voice their opinions and deny news institutions' negative portrayal. The second, citizen journalism, is a tool for news institutions in responding to the protesters' resistance. This is because protesters lack a solid and consistent perception of the issue, and the rejection of news institutions and journalists is no longer primary attention for them as soon as police officers attack news crews.The Black Lives Matter movement in 2020 has emerged through the help of social media and citizen journalism in spreading the news, responding to the incident, and mobilizing the protest against police brutality and racial discrimination against African Americans. Citizen journalism has become an alternative for Twitter users who distrust American journalism from mainstream news media. This study examined tweets of citizen journalism to see the discourse of American journalism on Twitter. Using Van Dijk’s Critical Discourse Analysis (CDA), this study finds positive and negative aspectse of citizen journalism. The first is that citizen journalism is an online resistance tool of protesters against news institutions where they can voice their opinions and deny news institutions' negative portrayal. The second, citizen journalism, is a tool for news institutions in responding to the protesters' resistance. This is because protesters lack a solid and consistent perception of the issue, and the rejection of news institutions and journalists is no longer primary attention for them as soon as police officers attack news crews.The Black Lives Matter movement in 2020 has emerged through the help of social media and citizen journalism in spreading the news, responding to the incident, and mobilizing the protest against police brutality and racial discrimination against African Americans. Citizen journalism has become an alternative for Twitter users who distrust American journalism from mainstream news media. This study examined tweets of citizen journalism to see the discourse of American journalism on Twitter. Using Van Dijk’s Critical Discourse Analysis (CDA), this study finds positive and negative aspectse of citizen journalism. The first is that citizen journalism is an online resistance tool of protesters against news institutions where they can voice their opinions and deny news institutions' negative portrayal. The second, citizen journalism, is a tool for news institutions in responding to the protesters' resistance. This is because protesters lack a solid and consistent perception of the issue, and the rejection of news institutions and journalists is no longer primary attention for them as soon as police officers attack news crews.The Black Lives Matter movement in 2020 has emerged through the help of social media and citizen journalism in spreading the news, responding to the incident, and mobilizing the protest against police brutality and racial discrimination against African Americans. Citizen journalism has become an alternative for Twitter users who distrust American journalism from mainstream news media. This study examined tweets of citizen journalism to see the discourse of American journalism on Twitter. Using Van Dijk’s Critical Discourse Analysis (CDA), this study finds positive and negative aspectse of citizen journalism. The first is that citizen journalism is an online resistance tool of protesters against news institutions where they can voice their opinions and deny news institutions' negative portrayal. The second, citizen journalism, is a tool for news institutions in responding to the protesters' resistance. This is because protesters lack a solid and consistent perception of the issue, and the rejection of news institutions and journalists is no longer primary attention for them as soon as police officers attack news crews.